Hymenoptera Venom Allergy: How Does Venom Immunotherapy Prevent Anaphylaxis From Bee and Wasp Stings? - Sahiner, Umit Murat; Durham, Stephen R. (Frontiers in Immunology, 2019)
Hymenoptera stings may cause both local and systemic allergic reactions and sometimes even life threatening anaphylaxis. Along with pharmaceutical drugs and foods, hymenoptera venom is one of the most common causes of anaphylaxis in humans. To date, no parameter has been identified that may predict which sensitized people will have a future anaphylactic reaction, however many risk factors such as mast cell activation syndromes associated with the severity of the re-sting reaction are known. Venom immunotherapy (VIT) is the most effective method of treatment for people who had systemic reactions to an insect sting, which is shown to be effective even after discontinuation of the therapy. Development of peripheral tolerance is the main mechanism during immunotherapy. It is mediated by the production of blocking IgG/IgG4 antibodies that may inhibit IgE dependent reactions through both high affinity (FcεRI) and low affinity (FcεRII) IgE receptors on mast cells, basophils and B cells. The generation of antigen specific regulatory T cells produces IL-10 and suppresses Th2 immunity and the immune responses shift towards a Th1-type response. B regulatory cells are also involved in the production of IL-10 and the development of long term immune tolerance. During VIT the number of effector cells in target organs also decreases, such as mast cells, basophils, innate type 2 lymphocytes and eosinophils. Several meta-analyses and randomised controlled studies have proved that VIT is effective for preventing systemic allergic reactions to a sting and improves the quality of life. In this review, the risk of systemic reactions and anaphylaxis in venom allergy and how VIT changed this risk are discussed.